Development and Contextualization of Multicultural Insight-Based Quran Hadith Materials in Madrasah Aliyah (EDUKASIA, 2020)
Indonesian Muslims are faced with the realities of life that are multi-ethnic, religious, cultural and linguistic. It must be responded critically as early as possible. The understanding of diversity (multiculturalism) should truly be the foundation of all components of the Muslim community without exception for the students. Therefore this paper intends to answer 1) material content of Quran Hadith with a multicultural perspective at Madrasah Aliyah Negeri 2 Pontianak, and 2) Development and contextualization of Qur'an Hadith material in daily life. This research was categorized as field research and literature study. Data collection methods used were observation, interviews and document analysis. Data analysis was through two models, namely content analysis and Miles and Huberman's model which involved analysis steps, namely: data collection, data reduction, data display, and verification. The authors’ findings on this study are that the content of the Quran Hadith with a multicultural perspective in Madrasah Aliyah is carried out by expanding the reading, the meaning of the implementation of tolerance, social ethics, justice, deliberation / democracy concepts which are constructed from the Islamic universal values and moderation (washathiyah) so they can foster a tolerant and empathy (alturism) attitutes to human beings as a manifestation of an obedient servant.